Educational Faculty Perceptions of the Learning Climate in a Juvenile Justice Residential Facility - Carolyn Cox; Joseph Visker; Ashley Hartman (Arizona State University, 2011)
The majority of educational faculty from a juvenile justice residential detention facility in rural Northeast Missouri who participated in a learning climate survey of their school seemed to agree that the environment for staff and students was generally physically safe and emotionally supportive; key factors for a positive learning climate. By describing perceptions of their schoolâs learning climate; facility educational faculty can identify strengths and improve upon weaknesses. Enhancing a schoolâs physical and psychosocial surroundings leads to a healthier school environment for all.